Testes de bondade de ajuste para a distribuição Birnbaum-Saunders. - TSUYUGUCHI, Aline Barbosa. (2012)
Submitted by Johnny Rodrigues (johnnyrodrigues@ufcg.edu.br) on 2018-08-02T21:21:48Z No. of bitstreams: 1 ALINE BARBOSA TSUYUGUCHI - DISSERTAÇÃO PPGMAT 2012..pdf: 613833 bytes, checksum: c354cd90842e461c0fb29b0ee5f925d3 (MD5)